Role of plant genetic resources in encountering climate change challenge. Issue 1 (March 2021) - Ichsan, C N; Darusman; Sulaiman, M I; Andini, R
Abstract: The world is encountering a global threat: climate change. It is estimated that the average air temperature will raise 3.7 - 7.8 °C by 2100. The possible impacts will vary, however, agriculture will be adversely affected marked with yield loss of staple crops such as rice and maize and altered post-harvest quality of horticulture products. On the other hand, the world Food and Agriculture Organization (UN-FAO) has set a target ' zero hunger ' by 2030', despite the five big challenges ahead: i) protracted conflict, ii) growing inequality, iii) rapid urbanization, iv) economic challenges, v) drought and natural disasters. The existing plant genetic resources, particularly the wild, neglected, and underutilized species has a great role and bears big potential to be exploited and targetted to achieve food and nutrition security, esp . in the densely populated regions with malnutrition problem e.g. in Asia and sub-Saharan regions. However, a key to future and sustainable crop production lies in the collection of crop and their wild relatives stored in ex -situ, or in -situ. This paper aims to explain the importance of plant genetic resources as well as the potential of some underutilized crops closely attributed with drought resistence, such as sorghum ( Sorghum bicolor L. Moench), amaranth ( Amaranthus sp.). These crops bear potential to support national food security program.